2019
DOI: 10.3765/plsa.v4i1.4514
|View full text |Cite
|
Sign up to set email alerts
|

Grammatical convergence or microvariation? Subject doubling in English in a French dominant town

Abstract: In French, subject doubling is “quite common” (e.g. Nadasdi 1995, Auger 1998, Thibault 1983, Zahler 2014) but in English it is rare (Southard & Muller 1998). Yet when anglophones speak French, they use subject doubling with French patterns (Nagy et al. 2003). In this paper, we analyze subject doubling in English in a bilingual French-English town. Usinga large corpus and statistical modelling, we show that thereis no difference between language groups, and neither sex, education nor job type are significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Kapuskasing was founded in the 1920s with an economy driven by pulp and paper, which remains the dominant industry (Dunlap, 2017; Town of Kapuskasing, 2010). The community has a strong religious tradition, a bent toward outdoor activities, and close-knit social networks (Tagliamonte & Jankowski, 2019:4).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Kapuskasing was founded in the 1920s with an economy driven by pulp and paper, which remains the dominant industry (Dunlap, 2017; Town of Kapuskasing, 2010). The community has a strong religious tradition, a bent toward outdoor activities, and close-knit social networks (Tagliamonte & Jankowski, 2019:4).…”
Section: Methodsmentioning
confidence: 99%
“…(2003:82) included all strong third-person subjects, both pronouns and noun phrases, we restrict the present analysis to noun phrase subjects only. This is because Tagliamonte and Jankowski (2019:4-5) found that noun phrases exhibited a rate of 10% SD ( n = 6828) in Kapuskasing, whereas subjects outside of first- and third-person contexts, as in the second-person in (9), represented little more than 1% of the data.…”
Section: Circumscribing the Variable Contextmentioning
confidence: 98%
See 3 more Smart Citations